2017
DOI: 10.4162/nrp.2017.11.3.240
|View full text |Cite
|
Sign up to set email alerts
|

Preconceptional use of folic acid and knowledge about folic acid among low-income pregnant women in Korea

Abstract: BACKGROUND/OBJECTIVESFolic acid supplementation before pregnancy is known to significantly reduce the risk of having a baby with neural tube defects (NTDs). Therefore, it is important for women to be aware of the effects of folic acid supplementation before pregnancy. The purpose of this study was to investigate the awareness and preconceptional use of folic acid and to assess the current knowledge about folic acid among low-income pregnant women in Korea.SUBJECTS/METHODSA questionnaire survey was conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 26 publications
8
17
0
Order By: Relevance
“…Nilsen and collegues also found a better preconceptional FA intake associated with higher maternal age, higher education, and lower parity which is consistent with our study [16]. Several other studies also found that preconceptional FA intake is higher among mothers with higher education [17, 1921]. Therefore, Sri Lanka should pay further attention on education of the adolescent girls in the country.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Nilsen and collegues also found a better preconceptional FA intake associated with higher maternal age, higher education, and lower parity which is consistent with our study [16]. Several other studies also found that preconceptional FA intake is higher among mothers with higher education [17, 1921]. Therefore, Sri Lanka should pay further attention on education of the adolescent girls in the country.…”
Section: Discussionsupporting
confidence: 91%
“…It is satisfactory compared to a study done in Kandy, Sri Lanka where preconceptional FA consumption among two groups; mothers with and without children with neural tube defects (NTD) was 0% and 13% respectively [14]. Many researchers have found a low preconceptional FA intake among mothers in many communities [15–17]. Some studies stressed on the low preconceptional FA intake even though many participants have heard about FA [15, 1719].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It is likely that many Korean women became aware of folic acid after marriage or pregnancy. In a previous study, the majority (97.9%) of pregnant Korean women were reported to have heard of folic acid, 72% had knowledge of folic acid, and 24.6% had experience taking folic acid supplements starting at least 1 month before conception [ 18 ]. These proportions were much higher than those of the non-pregnant women in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Factors influencing folic acid supplementation during pregnancy among Korean women include planned pregnancy, experience of previous spontaneous abortions, and knowledge of the importance of folic acid [ 17 18 ]. However, there has been no published information on the factors associated with folic acid supplement use among non-pregnant Korean women of childbearing age.…”
Section: Introductionmentioning
confidence: 99%